A Guide to the Marine Isopod Crustacea of Pacific Costa Rica - Brusca, Richard C. (2024)
The marine isopad crustaceans known from, or expected to occur on Pacific Costa Rican shores are presented. Keys, diagnoses, synonymies and figures are given for 37 species, in 14 families. Five previously undescribed species are included, three of which are formally named and described: Metacirolana costaricensis n. sp., Rocinela murilloi n. sp., and Cyalhura guarocnsis n. sp. A general overview of oceanographic aspects of Pacific Costa Rican waters is given, as well as a brief review of biological studies that have been published concerning Costa Rican shores. An introduction to the anatomy and general biology of isopods is presented, which includes a somewhat detailed discussion of head appendages.